J Med Sci Res. 2015
DOI: 10.17727/jmsr.2015/3-037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic heterogeneity in Wilson disease - A review

Abstract: Wilson disease (WD) is an inborn error of copper metabolism leading to its accumulation in liver, kidney and cornea. It is caused by a defective ATPase protein which is coded by ATP7B gene. It follows an autosomal recessive mode of inheritance with a prevalence of 1 in 30,000. WD shows varied clinical heterogeneity making clinical diagnosis a difficult task. The corneal Kayser-Fleischer (KF) ring is an important diagnostic criterion as it is invariably present in 95% of the WD cases. In this review, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Analysis of clinical records of forty cases revealed that Kayser-Fleischer (KF) ring was present in corneas of 75% of cases at the time of diagnosis ( Table 2 ). According to Rangaraju et al, 2015 KF ring is detected in corneas of 95% of WD cases [ 15 ] which is not consistent with our data. Possible explanations for this difference can be nonappearance of detectable KF ring in cases with hepatic manifestation and early staging of disease in children as 7/10 cases without KF ring had only hepatic symptoms whereas 8/10 cases were ≤ 15 years of age ( Table 2 ) [ 19 , 20 ] Clinical details of cases showed that all forty cases had high urinary copper concentration and low serum ceruloplasmin levels.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Analysis of clinical records of forty cases revealed that Kayser-Fleischer (KF) ring was present in corneas of 75% of cases at the time of diagnosis ( Table 2 ). According to Rangaraju et al, 2015 KF ring is detected in corneas of 95% of WD cases [ 15 ] which is not consistent with our data. Possible explanations for this difference can be nonappearance of detectable KF ring in cases with hepatic manifestation and early staging of disease in children as 7/10 cases without KF ring had only hepatic symptoms whereas 8/10 cases were ≤ 15 years of age ( Table 2 ) [ 19 , 20 ] Clinical details of cases showed that all forty cases had high urinary copper concentration and low serum ceruloplasmin levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Clinical presentation of Wilson disease (WD) is very heterogeneous with predominant reports of hepatic, neurologic, and ophthalmic involvement along with multiple other abnormalities ranging from hemolytic anemia, thrombocytopenia, renal and gynecological problems as well as bone and muscle issues [ 15 ]. Disease may remain undetected initially and in most of the cases it is diagnosed after substantial damage to liver making liver transplantation the only treatment option [ 15 ]. Genetic diagnosis provides early disease detection which may help to reduce disease associated morbidity and high mortality especially in high-risk consanguineous populations such as our Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations